Studies in monetary economics - Patinkin, Don. (New York : Harper & Row, 1972)
The major purpose of this book is to bring together, in a convenient form, various papers that the author had written since the appearance of the second edition. These had to do with the reaction of various monetary mechanism, prices, interest rates, money and the theory of money etc.in the economy of a nation.
Includes index
Bibliography: p. 243-252.
usc 09/04/18
Loans
Keywords: Monetary policy